Analisis Kandungan Reduktor pada Paprika Merah dan Cabai Hijau Besar (Capsicum annum L.) Menggunakan Metode Spektrofotometri melalui Reaksi Redoks dengan Triiodida - Nuraini Harmastuti; Ahmad Ferdinansyah Rafsanjani; Hery Muhamad Ansory; Mira Dia Nofia (Jurnal Farmasi Indonesia, 2024)
The determination of reducing compounds in plant samples is continuously developed to achieve more practical and efficient analytical methods. This study analyzed the reducing compound content in red bell peppers and large green chilies using UV-Vis spectrophotometry via a redox reaction with triiodide. The results showed that this method can effectively determine reducing compounds in plant samples. The large green chili sample contained 0.01723% reducing compounds, whereas the red bell pepper sample exhibited a higher content of 0.0267%. These findings indicate that red bell peppers have a higher concentration of reducing compounds than large green chilies. This method has the potential to be a reliable approach for analyzing reducing agents in plants and can be further developed for pharmaceutical and food analysis applications.